Visual cultures of death in Central Europe : contemplation and commemoration in early modern Poland-Lithuania - Koutny-Jones, Aleksandra (Northern world, 2015)
In Visual Cultures of Death in Central Europe, Aleksandra Koutny-Jones explores the emergence of a remarkable cultural preoccupation with death in Poland-Lithuania (1569-1795). Examining why such interests resonated so strongly in the Baroque art of this Commonwealth, she argues that the printing revolution, the impact of the Counter-Reformation, and multiple afflictions suffered by Poland-Lithuania all contributed to a deep cultural concern with mortality. Introducing readers to a range of art, architecture and material culture, this study considers various visual evocations of death including 'Dance of Death' imagery, funerary decorations, coffin portraiture, tomb chapels and religious landscapes. These, Koutny-Jones argues, engaged with wider European cultures of contemplation and commemoration, while also being critically adapted to the specific context of Poland-Lithuania.